Investigation of anisakis infection and allergic potential on largehead hairtail (Trichiurus lepturus) from south coast of Yogyakarta Indonesia - Prima Putra, Masagus Muhammad; Busyro, Ihda Khozainul; Puspita, Indun Dewi; Setyobudi, Eko (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Anisakis spp. are parasites distributed worldwide that often infect marine fish species. This study investigated the prevalence, mean intensity, and Anisakis larvae species, and identified the allergenic potential of T. lepturus caught in the southern coasts of Yogyakarta, Indonesia. In total, 50 fish that were caught by the fishermen were measured for length and weight and examined for Anisakis larvae infection. The results showed that larvae were found in the abdominal cavity (87.03%), organs (7.95%), gonads (2.93%), and digestive systems (2.09%). The prevalence of Anisakis infection was high (64%), with a mean intensity of 7.47 larvae/fish. Molecular analysis revealed that the nematode was Anisakis typica. Therefore, it poses a potential health risk to humans. Consuming fish infected with Anisakis can cause allergic reactions even after the fish has been cooked. The identification was done through protein profile antigen detection of fish flesh, both infected and non-infected, using SDS-PAGE. In this study, the heating process was applied (60, 90, and 120) for 15 minutes. The result of allergenic potential detection from T. lepturus infected by Anisakis showed four protein bands correlated with Anisakis allergens Ani s 1 (24 kDa), Ani s 2 (97 kDa), Ani s 3 (41 kDa), and Ani s 7 (139 kDa) in all the infected fish, both fresh and processed.Keywords:AnisakisAllergenInfectionIntensityPrevalence